Evaluación Agronómica De Plantas De Café Arábigo Mediante Dos Sistemas De Crianza Y Tres Alternativas De Fertilización A Nivel De Vivero - Ulloa Zamora, Alex Fernando (2019)
The investigation was carried out in the estate of Mr. Juan Jiménez Becerra estate, located in the community of La Pita, Caluma canton, province of Bolívar. The area corresponds to low montane humid forest (bhmb). With characteristics: altitude of 237 meters above sea level, coordinates UTM X: 693815,12 Y: 9819618,37, with an average annual temperature of 22 ° C, maximum temperature of 24 ° C, minimum temperature of 19 ° C., with average annual rainfall of 1100 mm, average annual heliophanage of 720 hours / light / year and with a relative humidity of 80%. The objectives of the research were: Evaluate two systems of seedlings of Arabic coffee seedlings; Evaluate three fertilization alternatives in the vegetative development of coffee seedlings in nursery; and Determine the economic benefit of technological alternatives for raising coffee trees in nursery. The experiment was established in a randomized complete block design under an orthogonal design L9 (3) 4 corresponding to a 4-factor trial (containers, fertilizers, seaweed biostimulant and amino acid based biostimulant) on 3 levels each, according to the Taguchi Method and for the separation of means, the Tukey test was used. For the raising of arabica coffee seedlings at nursery level, it is indicated that the best results for study variables were obtained with black polyethylene sheaths, with the use of chicken bark in the substrate and that seaweed-based foliates promote and improve the plant quality The optimal response according to Taguchi method, was given with the use of 6 x 8 ”black sheath, 10% Ecoabonaza application on the substrate, two applications of algae-based product and that the T1 registration treatment is the best option since the point of view of the marginal rate of return